The Effect of Affiliative Motivation on Empathy and Prosocial Behavior of Madrasah Aliyah Ma’had Al-Zaytun’s Students - Siti Yolanda Hazri (Jurnal Penelitian Humaniora, 2018)
This study was aimed at determining the effect of affiliation motivation on empathy of students of Madrasah Aliyah Ma'had Al-Zaytun and determining the effect of affiliate motivation on the prosocial behavior of students of Madrasah Aliyah Ma'had Al-Zaytun. This research was an ex-post facto study with a quantitative approach. This research was conducted at the Islamic Boarding School of Mahad Al-Zaytun Islamic Boarding School in Indramayu West Java in March 2017 in the odd semester of the 2016/2017 academic year. The sample used in the study material was 372 students from a total population of 1064 students. Sampling was done by non-probability sampling techniques using a scale that refers to the Likert model. The data analysis technique in this study was Simple Regression analysis. The results of the study show that there is a significant effect of affiliate motivation on empathy on students in Madrasah Aliyah Ma'had Al-Zaytun with a determination coefficient of 24.2%. Second, there is a significant influence of affiliate motivation on prosocial behavior in students at Madrasah Aliyah Ma'had Al-Zaytun with a determination coefficient of 33.5%Pengaruh Motivasi Afiliasi Terhadap Empati dan Perilaku Prososial Siswa Madrasah Aliyah Ma’had Al-Zaytun.Penelitian ini bertujuan untuk mengetahui pengaruh motivasi afiliasi terhadap (1) empati siswa Madrasah Aliyah Ma’had Al-Zaytun dan (2) perilaku prososial siswa Madrasah Aliyah Ma’had Al-Zaytun. Penelitian ini merupakan penelitian ex-post facto dengan pendekatan kuantitatif. Penelitian ini dilaksanakan di Madrasah Aliyah Pesantren Mahad Al-Zaytun Indramayu Jawa Barat pada bulan Maret 2017 di semester ganjil tahun akademik 2016/2017. Sampel yang digunakan dalam bahan penelitian sebanyak 372 siswa dari total populasi 1064 siswa. Pengambilan sampel dilakukan dengan teknik non probability sampling menggunakan skala yang mengacu pada model Likert. Teknik analisis data pada penelitian ini menggunakan teknik analisis Regresi Sederhana Hasil penelitian menunjukkan bahwa terdapat pengaruh motivasi afiliasi yang signifikan terhadap empati pada siswa di Madrasah Aliyah Ma’had Al-Zaytun dengan nilai koefisien determinasi sebesar 24,2%. Kedua, Terdapat pengaruh motivasi afiliasi yang signifikan terhadap perilaku prososial pada siswa di Madrasah Aliyah Ma’had Al-Zaytun dengan nilai koefisien determinasi sebesar 33,5%.